2021
DOI: 10.3390/rs13173357
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Vegetation Change and Its Potential Drivers in Inner Mongolia from 2000 to 2019

Abstract: Inner Mongolia in China is a typically arid and semi-arid region with vegetation prominently affected by global warming and human activities. Therefore, investigating the past and future vegetation change and its impact mechanism is important for assessing the stability of the ecosystem and the ecological policy formulation. Vegetation changes, sustainability characteristics, and the mechanism of natural and anthropogenic effects in Inner Mongolia during 2000–2019 were examined using moderate resolution imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 81 publications
(98 reference statements)
4
28
1
Order By: Relevance
“…The Theil–Sen median method (capable of reflecting trend changes) and the Mann–Kendall (M–K) method (which assesses the significance of trend changes) were used for vegetation trend analysis over long time series [ 16 , 34 ]. Compared with the common linear regression method for assessing interannual variations in vegetation changes, the methods proposed here have a stronger ability to avoid data error and reduce the influence of outliers while increasing the accuracy and reliability of the analytical test results.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Theil–Sen median method (capable of reflecting trend changes) and the Mann–Kendall (M–K) method (which assesses the significance of trend changes) were used for vegetation trend analysis over long time series [ 16 , 34 ]. Compared with the common linear regression method for assessing interannual variations in vegetation changes, the methods proposed here have a stronger ability to avoid data error and reduce the influence of outliers while increasing the accuracy and reliability of the analytical test results.…”
Section: Methodsmentioning
confidence: 99%
“…Gao et al found that precipitation was the most important factor affecting the variation of NDVI in the Three-River Headwater Region [ 15 ]. Yao et al found that annual precipitation was the first dominant factor affecting vegetation growth in Inner Mongolia [ 16 ]. Chen et al studied the impact of climate change and human activities on grasslands in Central Asia, and found that precipitation was the main climatic factor affecting grassland dynamics in Central Asia, and overgrazing accelerated grassland degradation [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Combining the process with the Sentinel dataset or other vegetation indexes (e.g., EVI, SAVI) may help to obtain more precise estimates of vegetation dynamics. Last but not least, if breakpoints, which indicate a shift in the mechanism of influence on the time series under certain circumstances, are neglected, the results of the trend analysis may lead to a misjudging of the factors that influence vegetation changes [40]. In future studies, the times at which breakpoints occurred should be first identified, noting points at which the time series was split into sub-series.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…emote Sens. 2022, 14, 3320 19 of 2 neglected, the results of the trend analysis may lead to a misjudging of the factors tha influence vegetation changes [40]. In future studies, the times at which breakpoints oc curred should be first identified, noting points at which the time series was split into sub series.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
See 1 more Smart Citation